Evaluation of the physicochemical properties and push-out bond strength of mta-based root canal cement - Chávez-Andrade, Gisele Moraima [UNESP]; Kuga, Milton Carlos [UNESP]; Duarte, Marco Antonio Hungaro; Leonardo, Renato de Toledo [UNESP]; Keine, Katia Cristina [UNESP]; Sant 'anna-Junior, Arnaldo; Só, Marcus Vinicius Reis (Jaypee Brothers Medical Publishing, 2013)
Aim: This study investigated the flowability, setting time, pH, calcium release and bond strength of a MTA-based cement (MTA Fillapex®) compared to AH Plus and Sealapex. Materials and methods: For the flowability test, the ISO 6876:2001 specification was utilized and for the setting time test, the ASTM C266-03 specification was utilized. For the pH and calcium release measurements, 10 samples were prepared for each group and analyzed for several different periods. For the push-out test, dentin disks were distributed into three groups, according to the cement utilized and into three subgroups, according to the root third (n = 10). After obturation, the specimens underwent push-out testing. The data were compared statistically using a significance level of 5%. Results: The flowability of all materials was found to be similar (p > 0.05). The setting times were different among the groups tested (MTA Fillapex < Sealapex < AH Plus) (p < 0.05). At days 7 and 28, the MTA Fillapex presented the higher pH values (p < 0.05). At 24 hours and at 14 days, the calcium release of the MTA Fillapex was similar to that of Sealapex (p > 0.05). AH Plus presented the lowest pH and calcium release values (p < 0.05). In all root thirds, the adhesion to the dentin of the MTA Fillapex and Sealapex were significantly lower than that of AH Plus (p < 0.05). Conclusion: MTA Fillapex and Sealapex presented several similar properties and both were found to be different than AH Plus. Clinical significance: This study evaluated the physicochemical and mechanical properties of new MTA-based root canal cement, in order to use this scaler in root canal fillings. MTA Fillapex showed satisfactory properties for clinical use.
Keywords: Adhesion; Calcium; MTA; pH; Push-out